A variant of the Agro-Chain greenhouse gas Emissions (ACE) calculator, including specific operation in rice chains, and simplified for target users (extension services) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The calculator is fully functional (describing all unit operations as agreed with Olam experts), filled with complete data sets (partly from literature and partly based on measurements by Olam).